2017
DOI: 10.1097/mao.0000000000001278
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Ménière's Disease With and Without Labyrinthectomy

Abstract: Objective: To investigate outcomes of cochlear implantation (CI) in patients with Ménière's disease (MD) with and without surgical labyrinthectomy. Study Design: Retrospective study. Setting: Multiple tertiary referral centers. Subjects: Thirty one ears from 27 patients (17 men, 10 women, aged 42–84) with CI in ipsilateral MD ear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 24 publications
6
34
0
2
Order By: Relevance
“…One disadvantage of simultaneous labyrinthectomy and CI is that patients with residual hearing preoperatively will not experience the full consequences of single sided deafness and may not fully appreciate the benefit of the cochlear implant. 10 In a study by Vermeire et al, after CI, the hearing of all seven subjects improved significantly. 11 In a study by Heywood et al, in two patients with simultaneous labyrinthectomy and cochlear implantation, there was complete resolution of vertigo; speech perception in quiet and ability to hear in background noise improved considerably.…”
Section: Discussionmentioning
confidence: 88%
“…One disadvantage of simultaneous labyrinthectomy and CI is that patients with residual hearing preoperatively will not experience the full consequences of single sided deafness and may not fully appreciate the benefit of the cochlear implant. 10 In a study by Vermeire et al, after CI, the hearing of all seven subjects improved significantly. 11 In a study by Heywood et al, in two patients with simultaneous labyrinthectomy and cochlear implantation, there was complete resolution of vertigo; speech perception in quiet and ability to hear in background noise improved considerably.…”
Section: Discussionmentioning
confidence: 88%
“…Investigations of cochlear implantation in Meniere's disease patients have demonstrated successful auditory rehabilitation in this and other studies. 24,26,27 Simultaneous labyrinthectomy and cochlear implantation provides many benefits, including the benefit of an ablative and restorative procedure under a single general anesthetic, restoration of binaural hearing, and the potential elimination of vertigo and tinnitus. Notably, all of our patients had complete resolution of their tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated successful audiologic rehabilitation of Meniere's disease patients with cochlear implantation . Simultaneous labyrinthectomy and cochlear implantation in patients with Meniere's disease provide a unique opportunity to address intractable vertigo and restore auditory perception in a deafened ear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, in a comparative study [53] between cochlear sacculotomy techniques and endolymphatic sac decompression, the control of vertigo was significantly better in patients after cochleo-sacculotomy but also with significant deterioration of hearing. The cochleo-sacculotomy procedure performed simultaneously with cochlear implant surgery in patients with deafness and persistent vertigo in Ménière's disease is an alternative already proposed by some authors [54][55][56], and they have reported good results.…”
Section: Sacculotomymentioning
confidence: 99%